1981
DOI: 10.1139/x81-015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of explant selection on the shoot-forming capacity of juvenile tissue of Pinusradiata

Abstract: The shoot-forming capacity of Pinusradiata D. Don juvenile explants under tissue culture conditions was examined. Three types of explant were used: whole embryos; cotyledons excised from whole embryos which had been cultured for 1 week on the shoot initiation medium; and cotyledons excised from 1-week-old aseptically germinated seeds. The average number of rootable shoots produced per seed in 12–13 weeks was 9 for excised embryos, 18 for their separated cotyledons, and 180 for the cotyledons from germinated se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
25
0
2

Year Published

1985
1985
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(34 citation statements)
references
References 0 publications
7
25
0
2
Order By: Relevance
“…With radiata pine, formation of meristematic tissue is a prerequisite for first-generation adventitious shoots (1). Meristematic tissue, which forms on whole embryos, seedling shoot tips, and excised cotyledons after three weeks on a cytokinin medium, subsequently forms shoots on a cytokinin-free medium (1,13,25,26).…”
Section: Introductionmentioning
confidence: 99%
“…With radiata pine, formation of meristematic tissue is a prerequisite for first-generation adventitious shoots (1). Meristematic tissue, which forms on whole embryos, seedling shoot tips, and excised cotyledons after three weeks on a cytokinin medium, subsequently forms shoots on a cytokinin-free medium (1,13,25,26).…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the present study was two-fold: (1) to develop a method for the induction of adventitious buds on two types of explant: excised whole embryos, and excised cotyledons from treated seeds of Brutian pine, (2) to stimulate the development of these buds into shoots. This is, we believe, the first published account of the development of a suitable procedure for the in vitro culture of this species.…”
Section: Introductionmentioning
confidence: 99%
“…Aitken et al (1981) found that the translucent shoots that formed on vitrified Pinus radiata cultures were slow to elongate, but grew into normal shoots if left on the same medium for 2 to 3 months. Aitken-Christie and Thorpe (1985) described three types of shoots that could be formed, i.e., waxy shoots, which were similar to seedling shoots, wet shoots, which were dark green with the needles stuck together and lacked abundant epicuticular waxes, and translucent shoots, which were water-soaked and did not survive transfer from in vitro conditions.…”
Section: Beneficial Managementmentioning
confidence: 99%